2002
DOI: 10.1210/jcem.87.1.8153
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the New Long-Acting Formulation of Lanreotide (Lanreotide Autogel) in the Management of Acromegaly

Abstract: Lanreotide Autogel is a new long-acting aqueous preparation of lanreotide for the treatment of acromegaly and is administered by deep sc injection from a small volume, prefilled syringe. The aim of this study was to evaluate the efficacy and safety of this new long-acting formulation in a large population of acromegalic patients previously responsive to lanreotide 30 mg, im (sustained release microparticle formulation). Lanreotide Autogel was administered by deep sc injection every 28 d to 107 patients (54 mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
100
0
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(114 citation statements)
references
References 18 publications
11
100
0
3
Order By: Relevance
“…While earlier studies reported a high success rate for firstgeneration SSAs, octreotide and lanreotide (3,4), more recent studies show that control of growth hormone (GH) and insulin-like growth factor 1 (IGF1) levels using stricter criteria is achieved in !40% of patients (5,6). Pasireotide is a multireceptor-targeted SSA that binds SSTR1, SSTR2, SSTR3 and SSTR5, with the highest affinity for SSTR5 (7).…”
Section: Introductionmentioning
confidence: 99%
“…While earlier studies reported a high success rate for firstgeneration SSAs, octreotide and lanreotide (3,4), more recent studies show that control of growth hormone (GH) and insulin-like growth factor 1 (IGF1) levels using stricter criteria is achieved in !40% of patients (5,6). Pasireotide is a multireceptor-targeted SSA that binds SSTR1, SSTR2, SSTR3 and SSTR5, with the highest affinity for SSTR5 (7).…”
Section: Introductionmentioning
confidence: 99%
“…Three long-acting formulations, namely octreotide LAR, lanreotide acetate, and an aqueous slow-release depot preparation (autogel) have been developed in an effort to increase the dosing interval and provide a more sustained clinical effect [16-18]. Previous studies [19-23] concluded that lanreotide acetate may be a safe and effective alternative therapy in patients with diffuse forms of CHI, offering an improved quality of life, since it is well tolerated and contributes to a clear simplification of the medical care.…”
Section: Discussionmentioning
confidence: 99%
“…Lanreotide Autogel (also referred to as lanreotide LAR or Somatuline) has been shown to have near identical efficacy to lanreotide SR in a few studies, including a fouryear follow-up study reported by Gutt et al [47,55,56]. Lanreotide Autogel has also been compared with octreotide LAR in two small cross-over studies, with no clear evidence of superiority for either drug [57,58].…”
Section: Secondary Medical Therapymentioning
confidence: 99%